Productive specialization and integration in South America: A global input–output analysis - Brondino, Gabriel (2023)
In the current context, where a large part of international trade in goods and services is linked to global production chains, the policy course to reap the gains from this trade differs according to the point of view adopted. While from a country's point of view, the strategy is to join global production chains and upgrade to higher value-added activities, from the point of view of the regions, the new scenario offers opportunities to deepen productive integration. In the present paper, we aim to examine the role played by South America in global production chains and the potential for strengthening regional integration. We observe that considering extra-regional markets, the region maintains a pattern of specialization biased towards the export of primary commodities. However, intra-regional trade is based on more technologically complex sectors with favorable prospects for promoting regional production chains.